Apple's custom chips : a genius decision? - Busse, Meghan R. (Meghan Ruth); Springer, Susan T. (London : Kellogg School of Management, 2022)
When Steve Jobs co-founded Apple in 1976, his philosophy was to move fast, unencumbered by norms, and take risks in search of greater rewards. His strategy was to differentiate Apple by developing high-end products that consumers craved.
Description based on XML content.
Keywords: elektronické knihy; Jobs, Steve, -- 1955-2011.; Apple Computer, Inc; electronic books; Computer industry -- United States; New products -- Management